Questions & Answers

Question

Answers

Answer

Verified

91.8k+ views

We are given an equation $m + 4\left( {2m - 3} \right) = - 3$ and we have been asked to find the value of $m$.

$ \Rightarrow m + 4\left( {2m - 3} \right) = - 3$

Step 1: Multiply the constant outside bracket with the terms inside brackets using distributive property.

$ \Rightarrow m + \left( {4 \times 2m} \right) - \left( {4 \times 3} \right) = - 3$

Step 2: Now, simplify the equation.

$ \Rightarrow m + 8m - 12 = - 3$

Step 3: Bring the like terms together and add them.

$ \Rightarrow 9m = 9$

Step 4: Shift to find the required value of $m$.

$ \Rightarrow m = \dfrac{9}{9} = 1$

Hence, $m = 1$.

An equation is simply an expression which has a sign of “equals”. But these equations are not simple. They can either be linear, quadratic, cubic, etc. This depends upon the degree of the equation. An equation with highest degree 1 is called a linear equation. The equation given in the question is a linear equation. An equation with highest degree 2 is called a quadratic equation, and that with the highest degree 3 is called a cubic equation.

Furthermore, these equations can be in one, two, three or many variables. Let us see certain examples.

1) $4x = 8$- this equation is a linear equation in one variable.

2) $3x + 6y = 18$ - this equation is a linear equation in two variables.

Students Also Read